2021
DOI: 10.1212/wnl.0000000000011846
|View full text |Cite
|
Sign up to set email alerts
|

Network-Related Changes in Neurotransmitters and Seizure Propagation During Rodent Epileptogenesis

Abstract: Objective:To test the hypothesis that glutamate and GABA are linked to the formation of epilepsy networks and the triggering of spontaneous seizures, we examined seizure initiation/propagation characteristics and neurotransmitter levels during epileptogenesis in a translationally relevant rodent model of mesial temporal lobe epilepsy.Methods:The glutamine synthetase (GS) inhibitor methionine sulfoximine was infused into one of the hippocampi in laboratory rats to create a seizure focus. Long-term video-intracr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
(85 reference statements)
0
8
0
Order By: Relevance
“… 2 Microdialysis studies reveal that the extracellular concentration of glutamate is indeed elevated both before and during seizure onset, suggesting that enhanced glutamate release and/or impaired uptake may occur in epilepsy. 3 , 4 It is well known that following a variety of brain insults including injury, infections, and acute seizures, astrocytes become “reactive,” changing their morphology, protein expression, and function. In line with elevated glutamate signaling in the epileptic brain, GLT-1 levels can be decreased in “reactive” astrocytes which would lead to elevated glutamate levels.…”
Section: Commentarymentioning
confidence: 99%
“… 2 Microdialysis studies reveal that the extracellular concentration of glutamate is indeed elevated both before and during seizure onset, suggesting that enhanced glutamate release and/or impaired uptake may occur in epilepsy. 3 , 4 It is well known that following a variety of brain insults including injury, infections, and acute seizures, astrocytes become “reactive,” changing their morphology, protein expression, and function. In line with elevated glutamate signaling in the epileptic brain, GLT-1 levels can be decreased in “reactive” astrocytes which would lead to elevated glutamate levels.…”
Section: Commentarymentioning
confidence: 99%
“…Glutamate is a well-known excitatory neurotransmitter and its accumulation in the brain is a contributing factor for seizure generation [ 37 ]. Moreover, our prior work confirmed that glutamate by the concentration of 5 mM for 8 h was sufficient for triggering ferroptosis in HT22 cells [ 12 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Besides, poorly controlled SE is one of the highest risk factors for chronic epileptogenesis ( Tong et al, 2022 ). Repetitive propagation of TLE seizures leads to additional brain damages in brain regions outside of initial focus which give rise to secondary epileptogenesis and comorbidities ( Dhaher et al, 2021 ). Thus, interfering with the NAc shell neurons of the TLE brain may not only confine acute seizure severity, but also may limit the development of drug-resistant epileptogenesis and related neurological comorbidities at the post-SE stages.…”
Section: Discussionmentioning
confidence: 99%